Regional climatic changes and their impact on the level of avalanche hazard in East Kazakhstan - Olga Petrova; Natalya Denissova; Gulzhan Daumova; Yelena Ivashchenko; Evgeny Sergazinov (Heliyon)
The article examines the territory of East Kazakhstan, where a sharply continental climate prevails with hot summers, cold and snowy winters. The mountainous regions of East Kazakhstan are represented by the Kalba, Altai and Saur-Tarbagatay ranges, they are surrounded by rolling plains. The highest points are at 3000–4500 m. On average, the heights are in the range of 900–1400 m. Despite the low heights in the mountainous area, the problem of avalanche safety is acute in the region. At the same time, the situation is complicated by not always predictable weather events, the frequency of which is increasing every year. These include heavy precipitation, sometimes combined with a sharp warming in winter, and the changing wind regime of the territory. To identify regional climate changes and its connection with the avalanche-prone situation in the region, the study analyzed meteorological data from weather stations located directly near avalanche prone locations over the past 23 years since 2001, as well as data from observations of avalanche-prone areas since 2005 and information on registered spontaneous avalanches from 2013 to the present. This study is the first in the East Kazakhstan region, which presents the results of a comprehensive analysis of data on 497 avalanche-prone sites, of which 325 sites pose a threat to life and infrastructure. 10 most dangerous sites have been selected for detailed study. The analysis of climate data was carried out based on information from 7 weather stations. The article discusses the main climatic changes in the region, including an increase in air temperature, an increase in precipitation and a change in wind conditions. Data from weather stations and snow measuring routes covering the period since 2005 have been used to develop probabilistic avalanche forecasts. The use of statistical methods and the analysis of the relationships between meteorological parameters (temperature, precipitation, wind speed) made it possible to build models predicting avalanche-prone situations. Data on spontaneous avalanches were analyzed for five sites (Bogatyrevskaya site, Prokhodnaya, Sogornoye-Barlyk, Tainty and Pikhtovka). Based on these data, equations of dependence of temperature, wind and precipitation have been developed, which improves the accuracy of forecasting avalanche risks. An analysis of the data in the Statistica program showed a significant relationship between sudden warming, increased wind speed and precipitation, which precedes avalanches. Regression equations and the approximation confidence coefficient for the average values of the studied parameters are obtained. The results of the study make it possible not only to establish patterns, but also to propose effective methods for monitoring and forecasting avalanche hazard in the region. According to the data analysis, regional features of climate change in East Kazakhstan were identified, and a comparison was made with previously known works on Kazakhstan. The interrelation of climatic characteristics with avalanche hazard in the region is shown. The results obtained in the study will help us to better understand the regional manifestations of climate change. An important task for further forecasting of avalanche activity is the correct design of the avalanche collection database. The authors identified information objects (entities). An ontological database model (Entity Relationship Diagram) is constructed. Based on it, a database has been created for a system for monitoring and forecasting avalanche activity in the East Kazakhstan region.